Development of a Target-Based Configurable Business-to-Business Model for Electronic Wholesale Information System in East Java - Liliana Liliana; Felix Handani; Bambang Prijambodo; Maria Christabella Wariky (Bina Nusantara University, 2023)
Until the end of 2021, most of the electronics wholesale market in East Java has found obstacles in contract administration and monitoring of consumers’ sales targets managed conventionally in contract management and sales target monitoring aspects. This phenomenon becomes complicated because most wholesaler systems have specific rules of management. The research discusses information systems that can be configured for various business processes in the wholesale sale of electronic goods. The case-study approach is applied by analyzing, designing, constructing, and validating the new proposed system based on three case studies with different business processes. The result of the analysis phase explains minimum sales value, the number of item variants in sales, verification rules for sales supervisors, and the configuration of user access rights that are highly flexible when applied. This system is developed as web-based to make easy access to multiple platforms to accommodate flexibility. The result summarizes that companies have the power of freedom to customize their target and help them to monitor wholesale store sales to meet sales target achievement. Alternatively, suppose companies create their new sub-companies with different targets and segments. In that case, they can easily configure target sales rules without spending significant money on developing another application.